Sonoelectroanalytical detection of lead at a bare copper electrode. - Tibbetts, D; Davis, J; Compton, R (2000)
The sonochemically facilitated, mercury free detection of Pb2+ at a copper electrode has been investigated as a means of simplifying the quantification of this important analyte and to minimise the interference of copper ion. The procedure relies upon maximising the formation of Pb-Cu intermetallic compounds leading to the emergence of a single, easily quantifiable stripping signal. Linear responses to Pb2+ were obtained with a sensitivity comparable to that obtained at a bare glassy carbon electrode. Interference from Cu2+, Zn2+ and Cd2+ was assessed on the copper electrode with no appreciable change in the Pb2+ voltammetric profile observed. In contrast, bare glassy carbon showed a significant change in Pb2+ voltammetric profile as Cu2+ was added, due to the formation of intermetallic species.